Kathu Pan 1 points and the assemblage-scale, probabilistic approach: a response to Rots and Plisson, "Projectiles and the abuse of the use-wear method in a search for impact". (February 2015) - Wilkins, Jayne; Schoville, Benjamin J.; Brown, Kyle S.; Chazan, Michael
Abstract: Rots and Plisson (2014) question our conclusion that 500, 000-year-old points from Kathu Pan 1, South Africa were used as spear tips (Wilkins et al., 2012). However, their reinterpretation of the fractures we identify as diagnostic impact fractures are incorrect. Despite the assertion, knapping processes alone do not explain the basal modifications on the KP1 points. Although Rots and Plisson are critical of the edge damage distribution method, it provides objective, quantitative and statistical comparisons of experimental and archaeological datasets. The data we present stand as reliable evidence for early hafted hunting technology. We suggest that the disagreement stems from a differing perspective on how lithic functional studies should deal with equifinality and the challenge of confidently assessing stone tool function. Highlights: Rots and Plisson (2014) make conflicting interpretations about the Kathu Pan 1 points. Results of Wilkins et al. (2012) stand as reliable evidence for early spear technology. We use an assemblage-scale, probabilistic approach. It is an effective strategy for dealing with equifinality and assessing tool function.